Handbook of domestic violence intervention strategies : policies, programs, and legal remedies - Roberts, Albert R. (New York : Oxford University Press, 2002)
Using expert intervention strategies, this volume is designed to prepare professionals to meet the needs of women and children who have suffered from domestic violence. It focuses on the advances in legal remedies, programme developments, treatment protocols, and multidisciplinary perspectives.
Includes bibliographical references and index.
Keywords: Family violence -- United States; Marital violence -- United States; Abused women -- Services for -- United States